CONSTITUTIONAL PRIORITIES IN THE ORGANIZATION OF FORMS OF PUBLIC ADMINISTRATION (Journal of actual problems of jurisprudence, 2020)
The theme of the study contains the constitutional principles and constitutional requirements for the practical effective distribution of competent areas of government, subjects and points of power. The study analyzes the political influence of the presidential system of governance on the strategic development of the state. In addition, the constitutional requirements and the role of state power in ensuring public order and political stability in the direction of internal and external relations are discussed. As the main object of the study, the system of public administration of Kazakhstan, which has formed its place among the States of Central Asia, is analyzed. The aim of the study is a comprehensive analysis of the regularities of mechanisms of phased implementation of long-term ideas, as the main reference point of the strategic development plan of the sovereign country «Kazakhstan-2050» in the system of public administration in Kazakhstan. The problem of formation and systematization of regularities of mechanisms for the phased implementation of long-term ideas in the above-mentioned strategic development plan is an urgent priority initiative. The state can take a bold step not only by determining the future direction, but also to develop a clear system. In the period of modern global globalization, civilizational States, realizing the passed way, make bold predictions for the future. In order not to remain a global leader, developing every day, it is necessary to assess their future. The research paper describes the scientific foundations in these areas. The main results of our research work is the ranking of its sovereignty, formed on the world stage, original and self-serving in a short year, an independent state, which withdrew its sovereignty from the Soviet Government. The research paper reflects the results of diplomatic cooperation and the influence of state power in establishing relations with the States of Central Asia, as well as with the countries of the near and far abroad. The results of research work characterized by theoretical consistency, determined on the basis of methodological and scientific-methodological foundations, the consistency of results articles published in scientific journals on the part of the author, according to scientific principles of research, as well as a complete disclosure of the mechanism for preserving public order and political stability, along with strategic economic development in the management of public power. According to the Constitution, our state is an independent, democratic, legal state, which belongs to the presidential form of government. The formation and systematization of regularities of mechanisms for the phased implementation of long-term ideas in the development strategy “Kazakhstan-2050” is the most important goal for the state, and for the legal (educational) Institute a particularly valuable principle. The practical significance of the research work is that the main purpose of our Constitution is to preserve independence as Mangilik El, firmly adhering to the main principles based on the welfare of the people, peace and tranquility. Key words: state, power, constitutional, humanization of laws, legal policy, human rights system, legislative norms, strategic development, the constitutional control, constitutional law, law.